The Construction of Self in Relationships: Narratives and References to Mental States during Picture-Book Reading Interactions between Mothers and Children - Rollo, Dolores; Longobardi, Emiddia; Spataro, Pietro; Sulla, Francesco (Frontiers in Psychology, 2017)
Previous studies showed that mothers vary in the way in which they discuss past experiences with their children, since they can exhibit narrative (elaborative) or paradigmatic (repetitive) styles to different extents. Given this background, the aim of the present study was to analyze differences in the mothers’ use of narrative styles and Mental State Language (MSL), as a function of children’s age and gender. Thirty dyads consisting of mothers and their 4 to 6-year-old children were observed during a picture-book reading interaction. Maternal utterances were coded according to the categories described by Tessler and Nelson (1994), classifying each mother as Narrative or Paradigmatic. Eight categories of MSL were analyzed: Perceptual, Emotional (Positive and Negative), Volitional, Cognitive, Communicative and Moral. The results confirmed the existence of the two maternal styles observed in the earlier studies. Importantly, we found that the mothers of younger children were more narrative than paradigmatic, whereas the opposite pattern occurred for the mothers of older children (they were more paradigmatic than narrative). As concerns MSL, the results indicated that the use of Communicative terms was significantly more frequent for narrative than for paradigmatic mothers, and decreased linearly with children’s age. Lastly, the mothers of younger children referred their MSL more frequently to the book characters than to themselves or to the child. Taken together, these results support the idea that mothers adapt their narrative styles and MSL input to the growing abilities of their children, therefore contributing to the development of social understanding.